Imatinib mesylate exerts anti-proliferative effects on osteosarcoma cells and inhibits the tumour growth in immunocompetent murine models. - Bérengère Gobin; Gatien Moriceau; Benjamin Ory; Céline Charrier; Régis Brion; Frederic Blanchard; Françoise Redini; Dominique Heymann (PLoS ONE)
Osteosarcoma is the most common primary malignant bone tumour characterized by osteoid production and/or osteolytic lesions of bone. A lack of response to chemotherapeutic treatments shows the importance of exploring new therapeutic methods. Imatinib mesylate (Gleevec, Novartis Pharma), a tyrosine kinase inhibitor, was originally developed for the treatment of chronic myeloid leukemia. Several studies revealed that imatinib mesylate inhibits osteoclast differentiation through the M-CSFR pathway and activates osteoblast differentiation through PDGFR pathway, two key cells involved in the vicious cycle controlling the tumour development. The present study investigated the in vitro effects of imatinib mesylate on the proliferation, apoptosis, cell cycle, and migration ability of five osteosarcoma cell lines (human: MG-63, HOS; rat: OSRGA; mice: MOS-J, POS-1). Imatinib mesylate was also assessed as a curative and preventive treatment in two syngenic osteosarcoma models: MOS-J (mixed osteoblastic/osteolytic osteosarcoma) and POS-1 (undifferentiated osteosarcoma). Imatinib mesylate exhibited a dose-dependent anti-proliferative effect in all cell lines studied. The drug induced a G0/G1 cell cycle arrest in most cell lines, except for POS-1 and HOS cells that were blocked in the S phase. In addition, imatinib mesylate induced cell death and strongly inhibited osteosarcoma cell migration. In the MOS-J osteosarcoma model, oral administration of imatinib mesylate significantly inhibited the tumour development in both preventive and curative approaches. A phospho-receptor tyrosine kinase array kit revealed that PDGFRα, among 7 other receptors (PDFGFRβ, Axl, RYK, EGFR, EphA2 and 10, IGF1R), appears as one of the main molecular targets for imatinib mesylate. In the light of the present study and the literature, it would be particularly interesting to revisit therapeutic evaluation of imatinib mesylate in osteosarcoma according to the tyrosine-kinase receptor status of patients.